1923 N.H. Laws 138, § 7 - (:unkn) unknown (My University, 1923)
Any person or persons who shall sell, barter, hire, lend or give to any minor under the age of twenty-one years any pistol or revolver shall be deemed guilty of a misdemeanor and shall upon conviction thereof be fined not more than one hundred dollars or be imprisoned not more than three months, or both.
Keywords: TRANSFER - MINORS